The relationship between live streamers’ self-disclosure and consumers’ purchase intention: The parallel mediating role of psychological distance and perceived homophily - Yi Liu (PLoS ONE, 2026)
As live streaming commerce continues to expand rapidly, the role of live streamers has emerged as a crucial factor. In an online environment with increasingly fierce competition and increasingly rich emotional needs of consumers, live streamers have gradually shown more self-disclosure to attract more consumers’ attention. While existing studies have indicated that the communication styles adopted by live streamers constitute a key factor influencing consumers’ purchasing behaviors, little is known about live streamers’ self-disclosure, a specific communication mechanism, is associated with consumers’ purchase intention, as well as the roles that psychological distance and perceived homophily between consumers and live streamers play in this process. Drawing on Social Penetration Theory, this study investigates the association between live streamers’ self-disclosure and consumers’ purchase intention, and analyzes the parallel mediating roles of psychological distance and perceived homophily in this relationship. The investigation employs regression analysis to examine 306 survey responses gathered from Chinese consumers. The results reveal that live streamers’ self-disclosure is positively associated with consumers’ purchase intention by diminishing the psychological distance between live streamers and consumers and enhancing perceived homophily; notably, psychological distance and perceived homophily exert significant parallel mediating effects in the association between live streamers’ self-disclosure and consumers’ purchase intention. Live streamers’ self-disclosure is linked to reduced audience psychological defensiveness via increased closeness, and to stronger identification through heightened similarity perception; both pathways are equally important in relation to higher purchase intention. This study contributes to a better understanding of how live streamers’ self-disclosure in live streaming contexts relates to consumers’ purchase intention, as well as the roles of psychological distance and perceived homophily between consumers and live streamers. It also provides a theoretical basis and practical implications for live streamers to engage in positive self-disclosure, to build closer connections and identification with consumers by reducing psychological distance and enhancing perceived homophily, and ultimately to support higher consumers’ purchase intention as well as the competitiveness of e-commerce platforms and enterprises.